Perancangan dan Implementasi Sistem Antrian Online Berbasis Web Pada Kumaira Universitas Islam Sultan Agung - Mohammad Fawwazi Sya’bani; Nova Miranda; Siti Nur Rohmah; Faris Su’ud Subiakto; Rieska Ernawati (Pusat Riset dan Inovasi Nasional, 2025)
This research discusses the design and implementation of a web-based online queue system at the Kumaira canteen of Sultan Agung Islamic University to address long queues and inefficiencies in food ordering. Using the waterfall development method, this system is designed to allow customers to order food online, monitor stock availability, and make digital payments. The results indicate that this system enhances the canteen's operational efficiency, reduces customer waiting times, and simplifies transaction and stock management, ultimately providing a better experience for customers and improving staff productivity.